Nitrogen Fertilization on Growth and Yield Response of Oat (Avena Sativa L.) - Islam, MM; Mamun, AA; Ghosh, SK; Mondal, D (Bangladesh Agronomy Journal, 2021)
Nitrogen is one of the main inputs of oat cultivation and its efficient management is a basic for harvesting the maximum potentiality of the crop. An investigation was conducted at field laboratory of Agrotechnology Discipline, Khulna University, Bangladesh to find out the effect of nitrogen fertilizer on growth, yield and yield contributing characters of oat during 2017-2018. The experiment was designed in randomized complete block with seven N rates (0, 30, 45, 60, 75, 90 and 105 kg ha-1) in triplicate run. Application of N nitrogen significantly increased the growth and yield of oat. The results showed that 105 kg ha-1 N was supreme in all growth parameters and straw yield but 90 kg ha-1 N was better for main yield parameters and grain yield. The maximum plant height (101.27 cm), leaf number (11.90), tillers plant-1 (9.93), plant density (41.33 m-2) and straw yield (4.70 tha-1) were recorded with 105 kg ha-1 N application, whereas the highest grain yield (1.76 t ha-1) was found with 90 kg ha-1 N. From the results of the present research, it may be concluded that application of 90 kg N ha-1 could be used for oat production in soils of AEZ 13, Bangladesh. Bangladesh Agron. J. 2020, 23(2): 35-43